1986
DOI: 10.1177/0310057x8601400410
|View full text |Cite
|
Sign up to set email alerts
|

Costs, Severity of Illness and Outcome in Intensive Care

Abstract: Severity of illness (Therapeutic Index Severity Score, Classes 1-4) and direct clinical costs (labour costs, diagnostic costs, drugs, disposables, etc.) were determined for 100 consecutive patients admitted to Royal Newcastle Hospital Intensive Care Unit over six weeks. Outcome was assessed using mortality, quality of life, functional status, productivity and mental status one month after separation from the Unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 35 publications
3
35
0
2
Order By: Relevance
“…Although this cannot be expected in all situations, differences should be observable at least for groups of patients with a distinct prognosis. In the literature, non-survivors consistently show higher TISS values than survivors [9,12,13,14,15,16,17], which also could be demonstrated for the TISS-28 ( Fig. 4 and [4]).…”
Section: Discussionsupporting
confidence: 67%
“…Although this cannot be expected in all situations, differences should be observable at least for groups of patients with a distinct prognosis. In the literature, non-survivors consistently show higher TISS values than survivors [9,12,13,14,15,16,17], which also could be demonstrated for the TISS-28 ( Fig. 4 and [4]).…”
Section: Discussionsupporting
confidence: 67%
“…Although earlier studies have suggested a relationship between TISS and cost, the lack of data supporting this hypothesis was noted in previous reports [3,8]. In 1983, an Australian study of 100 patients estimated the average daily cost per patient to be $268 (Australian $) excluding central hospital costs, or $17/1983 TISS point [3].…”
Section: Discussionmentioning
confidence: 97%
“…The original publication of Cullen et al in 1974 included a small study which showed positive correlation between daily TISS and daily costs [1]. A detailed and larger scale Australian study in 1986 indicated a strong linear relationship between total TISS points and total admission costs [3]. There is a lack of data to verify this correlation in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…In an electronic literature search using Medline (January 1980 to December 1996) and HealthSTAR (January 1980 to December 1996), seven individual studies were identified which fulfilled the selection criteria of reporting patient‐specific costs in the ICU. From these studies, the following variables as predictors of daily cost were identified: medical vs. surgical patients [7, 8]; diagnosis [9, 10]; the Acute Physiology and Chronic Health Evaluation (APACHE) II severity score [11, 12]; elective or emergency admission [9, 10]; clinical severity [13]; workload units [9, 11]; mechanical ventilation [12]; length of ICU stay [11]; and survival [7–10, 12]. These variables were used in the subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%